2021
DOI: 10.7759/cureus.17596
|View full text |Cite
|
Sign up to set email alerts
|

Awake Craniotomy for Resection of Cerebral Arteriovenous Malformation: Initial Experience From a Low- and Middle-Income Country

Abstract: Bakhshi et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“… 22 Short-term post-operative complications included hemorrhage (n = 3) 22 , 32 , neurologic dysfunction including paresis (n = 3), hemiplegia (n = 10), dysphasia/aphasia (n = 6), cranial nerve dysfunction (n = 3), and pulmonary embolism (n = 1). 23 , 27 , 28 , 29 , 30 , 31 Almost all the complications/dysfunctions gradually improved on subsequent follow-ups. The 3 cases with hemorrhage underwent a craniotomy for evacuation.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“… 22 Short-term post-operative complications included hemorrhage (n = 3) 22 , 32 , neurologic dysfunction including paresis (n = 3), hemiplegia (n = 10), dysphasia/aphasia (n = 6), cranial nerve dysfunction (n = 3), and pulmonary embolism (n = 1). 23 , 27 , 28 , 29 , 30 , 31 Almost all the complications/dysfunctions gradually improved on subsequent follow-ups. The 3 cases with hemorrhage underwent a craniotomy for evacuation.…”
Section: Resultsmentioning
confidence: 93%
“… 23 The patient with mid dysphasia described by Gamble et al had completely resolved by her 6 weeks follow-up. 27 Bakhshi et al described a case of conductive dysphasia and memory impairment 6 h after the procedure, which was due to cerebral edema, thus Dexamethasone was started that resolved the symptoms in 36 h. 28 Nimmannitya et al reported slight difficulty of speech which completely resolved within a few days. 29 Out of the 7 cases reported by Wang et al 3 experienced deficits, all of which improved on follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Awake craniotomy (AC) is fast becoming the standard of care for the resection of brain tumors occurring in eloquent areas [1][2][3][4][5]. Up to 30% of patients undergoing AC can experience intraoperative seizures (IOS) [4].…”
Section: Introductionmentioning
confidence: 99%